The Influence of Risk Management Maturity on Organizational Performance in the Public Sector: A Systematic Literature Review - Zuardiansyah Adi Purnama; Rela Sari (BUGIS : Journal of Business, Technology, & Social Science, 2026)
This study analyzes the influence of risk management maturity on organizational performance in the public sector using a Systematic Literature Review of 20 journal articles published between 2018 and 2025. The findings show that most studies report a positive impact, including improvements in reputation, operational effectiveness, flexibility, resilience, and the achievement of strategic objectives. However, two studies report negative effects due to silo mentality, bureaucracy, and failure of integration. Contingency Theory emerges as the dominant theoretical framework in explaining this relationship. The study concludes that risk management maturity has the potential to enhance public sector performance, but its success depends on contextual factors and proper integration.